Indirect evaluation of device-endothelialization with cardiac-CT after transcatheter closure of atrial septal defect: how long should antiplatelet therapy last postoperatively?. (25th November 2020) - Yan, C; Li, L; Pan, X; Li, S; Li, H; Wan, L; Wang, L; Fang, W
Abstract: Background: After transcatheter closure of atrial septal defect (ASD), it is still unclear about the in-vivo process of device-endothelialization in humans, which determines the duration of antiplatelet therapy. Based on contrast-uptake within device, cardiac-CT might have the potential to assess device-endothelialization indirectly. Purpose: The study was conducted to investigate the status of device-endothelialization with cardiac-CT after transcatheter closure of ASD. Methods: After more than 6 months of transcatheter ASD closure, cardiac-CT was performed in 119 patients (48M/71F; age: 46.7±14.4 years). According to contrast-uptake within device, complete or incomplete device-endothelialization was determined. In the latter, it was further divided into partial-endothelialization (with filling-defect) and no-endothelialization (without filling-defect). Multivariate logistic regression was used to determine the risk factors of incomplete device-endothelialization. In addition, device-endothelialization was analyzed grossly and histopathologically in 7 patients. Results: During the implantation-period of 2.57±2.59 years, incomplete device-endothelialization was identified in 43.7% of patients (partial-endothelialization in 36 patients and no-endothelialization in 16 patients). Complete device-endothelialization occurred in 14.3% of patients during 0.5–1 year and 73.8% after one year. After 6-month antiplatelet therapy, migraine restarted in 15 patients with incomplete device-endothelialization and 3 patients with complete device-endothelialization. After one-year antiplatelet therapy, migraine was still detected in 4 of 15 patients with incomplete device-endothelialization. There was a significant association between high in-vivo device-thickness and incomplete device-endothelialization (P<0.001) after adjusted for confounding factors. Pathological findings from 7 patients corresponded well with cardiac-CT. Conclusions: Cardiac-CT had the potential to evaluate the status of device-endothelialization after transcatheter closure of ASD and there was a good clinico-pathological correlation. Incomplete device-endothelialization was common postoperatively in humans and was associated with device-oversizing. Further research is required to determine the appropriate duration of antiplatelet therapy after device implantation. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): National Natural Science Foundation of China